Method of identification bot profiles based on neural networks in recommendation systems - Meleshko, Yelyzaveta; Drieiev, Oleksandr; Drieieva, Hanna (Національний технічний університет "Харківський політехнічний інститут", 2020)
The subject matter of the article is the process of increased the information security of recommendation systems. The goal of this work is to develop a method of identification bot profiles in recommendation systems. In this work, the basic models of information attacks by the profile-injection method on recommendation systems were researched, the method of identification bot profiles in recommendation systems using the multilayer feedforward neural networkwas developed and the experiments to test the quality of its work were conducted. The developed method is to identify bot profiles that attempt to change item ratings in a recommendation system inorder to increase the occurrence frequency of target items in recommendation lists to all authentic users, or to certain segments of authentic users. When removing bot profiles' data from the database of the recommendation system before generating recommendation lists, the accuracy of the system and the correctness of recommendations are significantly increased, and authentic users get protection from information attacks. Random, Average and Popular attacks were used to model the attacks on a recommendation system. To identify bots, their ratings for system items were analyzed. The experiments have shown that the neural network that analyzes only the numbers of different ratings in a profile, detects bot profiles with high accuracy, that use Random attack regardless of the number of target items foreach bot. At the same time, the developed neural network can detect bots that use Average or Popular attacks only when they have several target items. Also, the results of the experiments show that type I errors, when the system identifies authentic users as bots, is very rarely appear in the developed method. To improve the accuracy of the neural network, there can add to analysis also other data of user profiles, such as the timestamp of each rating and as segments of items, which was rated.

Об’єктом дослідження цієї роботи є процес підвищення інформаційної безпеки рекомендаційних систем. Метою роботи є розробка методу ідентифікації акаунтів ботів у рекомендаційній системі. У цій роботі було розглянуто основні моделі інформаційних атак ін’єкцією профілів на рекомендаційні системи, розроблено метод ідентифікації профілів ботів у рекомендаційних системах за допомогою багатошарової нейронної мережі прямого поширення та проведені експерименти для перевірки якості його роботи. Розроблений метод полягає у виявлені профілів ботів, які намагаються змінити рейтинги об’єктів у рекомендаційній системі з метою підвищення потрапляння цільових об’єктів до списків рекомендацій усім автентичним користувачам, або певним сегментам автентичних користувачів. Вилучення виявлених профілів ботів з бази даних рекомендаційної системи перед обчисленням рекомендацій значно підвищує точність її роботи та достовірність рекомендацій, а також захищає користувачів системи від інформаційних атак. Для моделювання атаки на рекомендаційну систему було використано випадкову, середню та популярну атаки. Для розпізнавання ботів аналізувалися оцінки, які вони виставляли об’єктам системи. Як показали проведені експерименти, нейронна мережа, що аналізує лише кількість різних оцінок у профілі, з високою точністю виявляє профілі ботів, які використовують випадкову атаку незалежно від кількості цільових об’єктів у кожного боту. В той же час розроблена нейронна мережа може виявляти ботів, що використовують середню та популярну атаку, тільки тоді, коли вони мають декілька цілей. Також з результатів експериментів видно, що у розробленому методі досить рідко виникають помилки першого роду – коли система ідентифікує звичайних користувачів як ботів. Для підвищення точності роботи нейронної мережі, можна враховувати й інші параметри профілів користувачів, зокрема, час виставлення кожної оцінки, а також те, до яких сегментів відносяться оцінені у профілі об’єкти.
Метод ідентифікації профілів ботів на основі нейронних мереж у рекомендаційних системах
Keywords: information attacks; information security; Internet bots; інформаційні атаки; інформаційна безпека; Інтернет-боти